Various Uses of Blast Furnace Slag and Steel Slag in Concrete and Mortar: Review - Mariam Ibraheem M. Hussein; Mohammed M. Rasheed (Genius Journals, 2022)
This paper presents a review to study the ideas of previous researches on using slag as a concrete material to get rid of the damage caused by it as a result of its accumulation in nature. The research also includes the types of slag and its production methods. Slag is a non-metallic product resulting from the iron smelting process. It is considered an industrial waste that is harmful to the environment. Recently, many researchers have shed light on the use of these wastes in the field of construction in order to reduce their damage to the environment as well as take advantage of the properties that it's give to concrete to produce environmentally friendly concrete and also reduce the cost of producing building materials. The methods of using slag in the concrete differed. Some researchers used it as coarse aggregate and fine aggregate, and some used it as a cementitious material because it contains the same oxides as cement. The use of slag in concrete and mortar has given good results, and it has been concluded by looking at previous studies that the best percentage for using slag as coarse aggregate ranges from 30% to 40%, fine aggregate ranges from 20% to 30%, and cementitious materials up to 6%. The use of slag in concrete had a good effect on some properties of concrete, including compressive strength, split tensile strength, flexural strength, setting time, absorption, chloride penetration, and porosity
Keywords: Types of Slag; Blast Furnace Slag; Steel Slag; Slag in concrete.